Finite-time terminal synergetic control of a class of nonlinear systems with unmatched uncertainties. (10th October 2019) - Ahifar, Azadeh; Noei, Abolfazl Ranjbar; Rahmani, Zahra
Abstract: In this paper, the problem of finite-time tracking for nth-order uncertain nonlinear systems with unmatched uncertainties is addressed. Using a terminal synergetic manifold, a controller is provided to force the tracking error to the origin in finite time in the presence of unmatched uncertainties. With this method, chattering problem is completely removed without defining a new function. Lyapunov theory is used to prove the stability of the proposed method. The proposed controller provides the convergence of finite-time tracking error to zero by suitable performance that is theoretically analysed and proved through simulation.